If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + 4) = 3 Reorder the terms: -3(4 + t) = 3 (4 * -3 + t * -3) = 3 (-12 + -3t) = 3 Solving -12 + -3t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -3t = 3 + 12 Combine like terms: -12 + 12 = 0 0 + -3t = 3 + 12 -3t = 3 + 12 Combine like terms: 3 + 12 = 15 -3t = 15 Divide each side by '-3'. t = -5 Simplifying t = -5
| 3(2-z)*0.2=z | | (3x)+4=-11 | | 11(2+8x)-10(10-11x)=912 | | -2(x-18)=(-x/2+3)(-3) | | 12=4n-10 | | x^3=216 | | -5=-x+3 | | 6x+2+3x+17=10 | | 3n+6n=3-9 | | .6a-.75b=c | | 7(-2x+6)=126 | | 5a^2+20a+3=0 | | -3q+4=q | | 3(3x+4)+3(3x+4)=18x+30 | | 7x+4+4x+9=10x+3 | | 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x | | x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 |